2019
DOI: 10.1097/md.0000000000016198
|View full text |Cite
|
Sign up to set email alerts
|

Surgical treatment for pelvic lipomatosis using a bladder-sparing technique

Abstract: The aim of this study was to report the experience and long-term efficacy of a novel surgical treatment for pelvic lipomatosis (PL) using a combination of pelvic fat mass extirpation and ureteral reimplantation. Data of 8 patients with PL who underwent pelvic fat mass extirpation and ureteral reimplantation at our hospital from September 2010 to March 2018 were retrospectively reviewed. Demographics, serum creatinine level, radiographic changes, perioperative complications, and patient-reported outc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 22 publications
(25 reference statements)
0
13
0
Order By: Relevance
“…However, PL patients still face the problem of recurrent ureteral stricture caused by continued growth of pelvic fat after ureteral reimplantation. 2,19,29 On the one TherapeuTic advances in urology hand, the growing pelvic fat may compress the replanted ureter again, resulting in recurrent ureteral stricture. On the other hand, the growing pelvic fat may further increase the pressure in the bladder after pressing the bladder, resulting in poor urine drainage.…”
Section: Discussionmentioning
confidence: 99%
“…However, PL patients still face the problem of recurrent ureteral stricture caused by continued growth of pelvic fat after ureteral reimplantation. 2,19,29 On the one TherapeuTic advances in urology hand, the growing pelvic fat may compress the replanted ureter again, resulting in recurrent ureteral stricture. On the other hand, the growing pelvic fat may further increase the pressure in the bladder after pressing the bladder, resulting in poor urine drainage.…”
Section: Discussionmentioning
confidence: 99%
“…PL is a rare disease of benign proliferation. Because of the subtle symptoms of early PL, some elderly male patients may be missed, and the incidence may be under-estimated[ 7 ]. Subsequently, patients with advanced disease are troubled with haematuria, unendurable LUTS, or gastrointestinal symptoms, such as constipation, nausea, lower abdominal pain, or progressively increasing back pain.…”
Section: Discussionmentioning
confidence: 99%
“…First, such a procedure was reported by Halachmi et al [28] in 1996 using an ultrasonic-assisted lipectomy device. Ge et al [7] reported promising results in a series of eight patients who underwent laparoscopic bladder fat extirpation and B/L ureteric reimplantation with a median follow-up of 48.5 mo, and only one patient had recurrence at 49 mo. However, long-term efficacy is not available.…”
Section: Discussionmentioning
confidence: 99%
“…With the evolution of technology over the years, minimal-access bladder-sparing surgeries have been performed with a good success rate. Ge et al [7] published a series of eight cases (second largest series over a period of eight years) who underwent laparoscopic procedure with good outcomes. We present our experience of robotic-assisted bladder-sparing surgery with good short-term outcomes, and it is the first series from India.…”
Section: Introductionmentioning
confidence: 99%